Comparative reflections for a new constitutional justice model - Bernal Cano, Natalia (Jurídicas, 2009)
The following paper presents a new mixed model of constitutional justice as a result of the comparison of several similar procedures of constitutional monitoring due to the initiative of individuals within various countries. It then displays the main result of the doctoral thesis of Natalia Bernal Cano entitled “Monitoring the Constitutionality of the law on the appeal of an individual in Germany, Belgium, and Colombia. Comparative reflections for a new constitutional justice model” directed by the professor Otto Pfersmann and nominated to the Constitutional Council of the French Government for the best doctoral thesis of the year award on constitutional monitoring. The doctoral research is authorized to be published in Paris. Its contributions evidenced that the protection of fundamental rights and the protection of the Constitution always tend to stay together in all constitutional procedures, because of their equivalent value. The functional compatibility of the constitutional justice forms lies in this fundamental aspect. There are similarities not only with regard to the functions of constitutional procedures, but as well as their structural elements, increasingly similar, objective and subjective, from abstract and concrete constitutionality controls, which are articulated or mixed creating a new atypical and simplified figure or a new procedural physiognomy that strengthens the protection of fundamental rights of individuals.